Reference for determining Phillip's constant values and peak enhancement factor for the use of JONSWAP spectrum in Western Java Sea waters - Satriyo Panalaran; Suntoyo; Aries Sulisetyono; Dhany Arifianto; Andri Ramdhani; Widi Agoes Pratikto (Results in Engineering)
Several researchers have attempted to find a suitable spectrum model for Indonesian waters, but these references do not provide a common understanding of defining a spectrum model. This prompted the researcher to reassess the applicability of the wave spectrum model in Indonesia based on more appropriate data sources and systematic work procedures. This research is based on time series wave profile measurement data, which are then transformed into power spectral density curves (referred to as spectrum curves). From a number of obtained spectrum curves, this study aims to recommend key parameter values that indicate the shape of the spectrum in the western Java Sea so that it can be applied to the needs of marine building design. The procedures carried out in this study include: adjustment of the values of the key parameters of the JONSWAP spectrum (α and γ); matching against a number of spectrum models; evaluation of the distribution functions to define the values of α and γ; as well sensitivity test. The results of this study recommend α0.99= 0.00943 and γ0.99=2.11 for application in marine building design, as well α0.5= 0.00163 and γ0.5=1.07 for application in operational studies.